2019
DOI: 10.1002/ajh.25661
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical transplantation in high‐risk pediatric leukemia: A retrospective comparative analysis on behalf of the Spanish working Group for bone marrow transplantation in children (GETMON) and the Spanish Grupo for hematopoietic transplantation (GETH)

Abstract: A total of 192 pediatric patients, median age 8.6 years, with high-risk hematological malignancies, underwent haploidentical stem cell transplantation (haplo-HSCT) using post-transplantation cyclophosphamide (PT-Cy), or ex vivo T cell-depleted (TCD) graft platforms, from January 1999 to December 2016 in 10 centers in Spain. Some 41 patients received an unmanipulated graft followed by PT-Cy for graft-vs-host disease (GvHD) prophylaxis. A total of 151 patients were transplanted with CD3-depleted peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 34 publications
(44 reference statements)
6
39
2
Order By: Relevance
“…This study reports the accumulated experience of all Spanish centers performing haplo‐HSCTs for the pediatric population with NMDs, which corresponds to 13.9% of the cumulative activity of haplo‐HSCTs 30 . In our study, the 2‐year OS of 44.9% was lower than that in our reported series on malignant disorders (55.1%) 26 and that recently reported from various groups in NMDs, which also differed according to the diagnosis 2,12,28,29,36‐39 .…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…This study reports the accumulated experience of all Spanish centers performing haplo‐HSCTs for the pediatric population with NMDs, which corresponds to 13.9% of the cumulative activity of haplo‐HSCTs 30 . In our study, the 2‐year OS of 44.9% was lower than that in our reported series on malignant disorders (55.1%) 26 and that recently reported from various groups in NMDs, which also differed according to the diagnosis 2,12,28,29,36‐39 .…”
Section: Discussioncontrasting
confidence: 52%
“…Our group (the Spanish Working Group for Hematopoietic Transplantation) reported consistent results from the largest analysis of clinical outcomes in children when comparing the two platforms in pediatric hematologic malignancies. Our study showed 2‐year relapse‐free and GvHD‐free rates of 49.2% and 40.4%, respectively, with relapse the main cause of haplo‐HSCT failure 30 . Based on the results of this study, we conducted a retrospective and multicenter study aimed at analyzing the feasibility of haplo‐HSCT, reporting the outcomes of a Spanish cohort of children with NMDs who underwent the procedure, and proposing a shared future strategy for haplo‐HSCT.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Cooley et al observed that patients with AML with KIR-B/x donors experienced a 30% improvement in RFS compared with those with A/A donors ( 40 ). Subsequently, many further investigations confirmed this beneficial effect of the KIR-B haplotype on relapse and survival in patients with hematological malignancies ( 50 , 51 , 57 , 67 , 72 , 76 , 79 , 81 , 85 , 88 92 , 96 , 98 , 101 104 ). Five of these studies reported that the protection effects mainly existed in the KIR Cen-B locus ( 67 , 88 , 91 , 92 , 96 ).…”
Section: Kir and Transplant Outcomesmentioning
confidence: 84%
“…In addition to the technique of adoptive transfer, many studies have analyzed the effects of innate donor-recipient NK cell alloreactivity on GVHD in a clinical setting. The majority of studies did not report a significant association between these parameters ( 41 44 , 46 , 47 , 50 , 51 , 54 56 , 59 , 65 , 66 , 79 , 81 , 83 , 87 89 , 91 93 , 97 , 98 , 102 , 104 ), while some reported a protective effect ( 70 , 74 , 76 ). Moreover, several studies found that KIR ligand mismatch or receptor-ligand mismatch increased the risk of GVHD ( 45 , 57 , 60 , 64 , 68 , 80 ).…”
Section: Kir and Transplant Outcomesmentioning
confidence: 97%